2022
DOI: 10.3389/fmicb.2022.855651
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Non-histidine Domains of Histidine Kinase CHK1 Diminishes the Infectivity of Candida albicans in an Oral Mucosal Model

Abstract: ObjectivesThe histidine kinase (HK) CHK1 and other protein kinases in Candida albicans are key players in the development of hyphae. This study is designed to determine the functional roles of the S_Tkc domain (protein kinase) and the GAF domain of C. albicans CHK1 in hyphal formation and mucosal invasion.MethodsThe domain mutants CHK25 (ΔS_TkcCHK1/Δchk1) and CHK26 (ΔS_TkcΔgafCHK1/Δchk1) were first constructed by the his1-URA3-his1 method and confirmed by sequencing and Southern blots. A mouse tongue infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Reduced phagocytosis in vitro seems not to correlate with decreased colonization of mutants in tissues, since previous studies have shown that tissue loads of mutants with PPM loss were significantly reduced in disseminated murine and oral candidiasis models 12,49,50 . At the same time, they are easily killed by immune cells in vitro 12,21 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Reduced phagocytosis in vitro seems not to correlate with decreased colonization of mutants in tissues, since previous studies have shown that tissue loads of mutants with PPM loss were significantly reduced in disseminated murine and oral candidiasis models 12,49,50 . At the same time, they are easily killed by immune cells in vitro 12,21 .…”
Section: Resultsmentioning
confidence: 92%
“…3.8 | Mutants with less phagocytosis are readily killed in the presence of serum Reduced phagocytosis in vitro seems not to correlate with decreased colonization of mutants in tissues, since previous studies have shown that tissue loads of mutants with PPM loss were significantly reduced in disseminated murine and oral candidiasis models. 12,49,50 At the same time, they are easily killed by immune cells in vitro. 12,21 Following standard procedures, we exposed each mutant and WT strain to pre-opsonized murine macrophages or human neutrophils from serum to calculate the extent of fungal killing.…”
Section: Loss Of Ppm In Goa1δ and Nuo1δ Delays Phagocytosismentioning
confidence: 99%
“…The CHK1 gene in C. albicans is involved in various functions, including enhancing its virulence, upregulating the quorum sensing and enabling responses to stress [ 24 ]. Recent studies have highlighted the importance of CHK1 gene during oral mucosal infections, its plays a crucial role in mediating cross-kingdom interactions, which can potentially increase the cariogenic potential of these microbiomes within the oral cavity [ 23 , 25 , 26 ].…”
Section: Alteration Of Oral Microbiome Composition In Ecc Through Int...mentioning
confidence: 99%